Smell disorders in COVID-19 patients: role of olfactory training. Issue 8 (26th February 2021) - Zhang, Yu; Mei, Tao; Chen, Ying; Wang, Lina; Jiang, Lulian; Liu, Ke; Zhao, Liping; Luo, Ziyu; Chi, Wenxin; Zhu, Xiangyu
Abstract: Background: As the coronavirus disease 2019 (COVID-19) spread around the world, a surge of evidence suggests that smell disorders are common symptoms in COVID-19 infection. This dysfunction may cause loss of appetite, malnutrition, poisoning, and depression. Obviously, the impairment has a strong impact on the quality of life. Therefore, there is an urgent need to identify effective treatments. Various therapies have been studied to treat smell disorders after infection, and olfactory training (OT) is considered a promising treatment option. Assessing the effectiveness and safety of olfactory training for COVID-19 patients with smell disorders is the main purpose of this systematic review protocol. Methods: PubMed, EMBASE, MEDLINE, the Cochrane Library, Chinese National Knowledge Infrastructure, Chinese Biomedical Literature Database, Wanfang Database, ClinicalTrials.gov trials registry, and Chinese Clinical Trial Registry will be searched from January 2019 to January 2021. A combination of subject words and free text words will be applied in the searches. The language is limited to Chinese and English. The complete process will include study selection, data extraction, risk of bias assessment, and meta-analyses. Endnote X9.3 will be used to manage data screening. The statistical analysis will be completed by Review Manager V.5.3 (Cochrane Collaboration) or Stata V.16.0 software. Results: This proposed study will assess the effectiveness and safety of OT for COVID-19 patients with smell disorders. Conclusion: The conclusion of this study will provide evidence to prove the effectiveness and safety of olfactory training for COVID-19 patients with smell disorders. Ethics and dissemination: This protocol will not evaluate individual patient information or infringe patient rights and therefore does not require ethical approval. Registration: PEROSPERO CRD42020218009.